1998
DOI: 10.1046/j.1466-822x.1998.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

The nature of savanna heterogeneity in the Orinoco Basin

Abstract: Detrended Canonical Correspondence Analysis (DCCA) was used to describe the relationship between savanna environments and vegetation community composition in the Orinoco Basin. TWINSPAN derived three major types of savanna vegetation, each with its own floristic and physiognomic features. The first group reflected a plant association with species of Trachypogon occurring in moderately infertile soils with low water availability and high bulk density. This group is distributed mostly on hilltops and dissected p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…This limits plant growth in the later savanna types (Baruch and Go´mez, 1996). Similar overriding influence of nutrient availability on the composition and structure of tropical savannas has been reported in other studies from Venezuela and Colombia (Beard, 1953;San Jose´et al, 1998;Susach, 1989) and from Guyana, Surinam and Brazil (Goodland, 1966;Goodland and Pollard, 1973;Goldsmith, 1974;Lopes and Cox, 1977;Miranda et al, 2003;van Donselaar, 1965). In addition, it has been proposed that fertility edaphic gradients were the main cause for the vegetation gradual transformation from grassland or treeless savanna to the typical woody savanna (Goodland and Pollard, 1973;Lopes and Cox, 1977;Sarmiento and Monasterio, 1969).…”
Section: Article In Presssupporting
confidence: 67%
See 2 more Smart Citations
“…This limits plant growth in the later savanna types (Baruch and Go´mez, 1996). Similar overriding influence of nutrient availability on the composition and structure of tropical savannas has been reported in other studies from Venezuela and Colombia (Beard, 1953;San Jose´et al, 1998;Susach, 1989) and from Guyana, Surinam and Brazil (Goodland, 1966;Goodland and Pollard, 1973;Goldsmith, 1974;Lopes and Cox, 1977;Miranda et al, 2003;van Donselaar, 1965). In addition, it has been proposed that fertility edaphic gradients were the main cause for the vegetation gradual transformation from grassland or treeless savanna to the typical woody savanna (Goodland and Pollard, 1973;Lopes and Cox, 1977;Sarmiento and Monasterio, 1969).…”
Section: Article In Presssupporting
confidence: 67%
“…It separated the highland Type I sites, with 2-4 rainless months, from the other savanna types with 5-6 dry months each. San Jose´et al (1998) found that the length of the dry season was an important variable in the analysis of Venezuelan and Colombian lowland savannas. Soil texture was correlated with site ordination and defines the capacity of soils to retain nutrient and water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, should we assume that only the 15 × 10 6 km 2 of Africa that Grace et al (2006) classified as savanna are influenced by fire and that 50 years of fire suppression could, on average increase the total carbon in trees by circa 6 t ha −1 (Higgins et al , 2007a) we would expect fire suppression in Africa to allow an additional carbon storage of about 9 Pg which is less than simulated by the model. San José et al (1998a, b) and Grace et al (2006) suggest that fire suppression in savannas could increase carbon storage by almost 1 t ha −1 yr −1 which would translate into an increase of 67.5 PgC in 50 years for Africa. Scholes (2004) estimates that values between 0.3 and 0.6 t ha −1 yr −1 would be more appropriate for savannas, which would translate into an increase between 14 and 27 PgC in for Africa, assuming that biomass accumulation can only occur for 30 years.…”
Section: Resultsmentioning
confidence: 99%
“…, 1997; Hanan et al. , 1998; San José et al. , 1998; Abbadie et al , in prep.), but they emphasize different suites of variables and do not include the full range of diversity of structural types and bioclimatic conditions found along the grassland–forest continuum.…”
Section: Introductionmentioning
confidence: 98%